Analisis Kinerja Tenaga Kontrak Bidang Informasi dan Teknologi (IT) pada Dinas Komunikasi dan Informatika Provinsi Sumatera Selatan - Ahsani, Deswan; Zuber, Konar; Hakim, Arif Rahman (@-Publik: Jurnal Administrasi Publik, 2024)
The South Sumatra Province Communication and Informatics Service plays an important role in the fields of communication, informatics, coding and statistics. With the vision of "Advanced South Sumatra Based on Information and Communication Technology", this agency seeks to improve the quality of ICT human resources, infrastructure, bureaucratic reform, and support digital startups. However, there are several challenges such as the lack of human resources who are able to adapt quickly to digital transformation and less than optimal implementation of IT tasks. Therefore, reliable IT contract workers are needed to drive the success of digital transformation. This research uses a quantitative descriptive method by collecting data through questionnaires distributed to IT contract workers as well as interviews with several service staff. The research results show that the performance of IT contract workers is at a fairly good level, but there are several areas that require improvement, such as the development of technical skills and time management. Factors such as work environment, support from superiors, and availability of resources were also found to have a significant effect on performance. Recommendations are given to increase training and development, as well as improve the performance evaluation system for IT contract workers at the South Sumatra Province Communication and Information Service.